Development of the Australian Ageing Semantic Differential, a new instrument for measuring Australian medical student attitudes towards older people. (19th February 2019) - Wilson, Mark A. G.; Tran, Yvonne; Wilson, Ian; Kurrle, Susan
Abstract : Objective: This study outlines development of an instrument for measuring attitudes of medical students towards older people, the Australian Ageing Semantic Differential (AASD). Methods: Words for AASD scales were derived from the reflections of 151 third year medical students attending two Australian medical schools. A pilot study of the AASD was then undertaken with third year students at another medical school to confirm usability and reliability of the instrument. After slight modification, a larger study using the AASD was then undertaken of medical students attending the three institutions, in order to obtain sufficient data for exploratory factor analysis. Results: n = 321 (response rate 73%). Mean AASD score 73.2/114. Cronbach's α = 0.86. There was no evidence of sequence bias. Exploratory factor analysis (EFA) demonstrated four factors: Instrumentality; Personal Appeal; Experience; and Sociability. A lower mean instrumentality subscore for all students and a higher mean experience subscore for female students were noted. Conclusions: The AASD instrument proved internally reliable, and its use was generalisable to different groups of medical students. Its design ensured construct and face validity, and responses were not affected by sequencing bias. This study has revealed positive student attitudes towards older people. Variation in attitudes requires further investigation.